2008
DOI: 10.1152/ajprenal.00031.2008
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin can activate the epithelial sodium channel (ENaC) in microdissected mouse distal nephron

Abstract: Nesterov V, Dahlmann A, Bertog M, Korbmacher C. Trypsin can activate the epithelial sodium channel (ENaC) in microdissected mouse distal nephron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 61 publications
3
44
0
Order By: Relevance
“…35 It was recently shown that rats fed a 1% sodium diet expressed both full-length and cleaved ␥ENaC at the plasma membrane, whereas Na-depleted or aldosteronetreated rats mainly expressed the cleaved subunit. 36 In agreement, we 37 and others 36 recently demonstrated that trypsin can activate ENaC in microdissected mouse and rat distal nephron and that the stimulatory effect of trypsin was more pronounced in tubules from animals maintained on a standardsodium diet than animals maintained on a low-sodium diet. These findings demonstrate that ENaC can be activated by extracellular proteases in the native renal tubule under normal physiologic conditions and that the degree of proteolytic preactivation of ENaC by endogenous proteases will determine /ml), in a combination of plasminogen (1 mg/ml) and uPA (150 U/ml), in uPA (150 U/ml) alone, or in plasminogen (1 mg/ml) alone.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…35 It was recently shown that rats fed a 1% sodium diet expressed both full-length and cleaved ␥ENaC at the plasma membrane, whereas Na-depleted or aldosteronetreated rats mainly expressed the cleaved subunit. 36 In agreement, we 37 and others 36 recently demonstrated that trypsin can activate ENaC in microdissected mouse and rat distal nephron and that the stimulatory effect of trypsin was more pronounced in tubules from animals maintained on a standardsodium diet than animals maintained on a low-sodium diet. These findings demonstrate that ENaC can be activated by extracellular proteases in the native renal tubule under normal physiologic conditions and that the degree of proteolytic preactivation of ENaC by endogenous proteases will determine /ml), in a combination of plasminogen (1 mg/ml) and uPA (150 U/ml), in uPA (150 U/ml) alone, or in plasminogen (1 mg/ml) alone.…”
Section: Discussionsupporting
confidence: 84%
“…28 As recently reported, pretreatment of M-1 cells with a furin inhibitor largely augmented the stimulatory effect of trypsin on ENaC currents, whereas pretreatment with aprotinin had little effect. 37 Thus, to minimize ENaC activation by endogenous proteases, the confluent M-1 cells grown on filters were preincubated for 6 to 8 h before the experiment with the furin inhibitor dec-RVKR-cmk (decanoyl-Arg-Val-Lys-Arg-chloromethyl ketone from Calbiochem/Merck Biosciences GmbH, Schwalbach, Germany) which was added to the apical bath solution. A 10 mM stock solution of dec-RVKR-cmk was prepared in DMSO and was diluted to a final concentration of 40 M.…”
Section: Ussing Chambermentioning
confidence: 99%
“…Thus, trypsin IV may proteolytically activate ENaC expressed at the apical membrane of the renal collecting duct. We previously have shown that trypsin I can activate ENaC in microdissected mouse distal nephron tissue (14). Here, we have demonstrated the expression of trypsinogen IV mRNA in human proximal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, the sites at which trypsins cleave and activate ENaC have not yet been identified. The prototypical serine proteases trypsin I and chymotrypsin are commonly used as experimental tools to achieve maximal proteolytic ENaC activation (13,14). There is evidence that trypsin I is expressed in epithelial cells (15) and can be detected in human urine (16) (Human Urine, PeptideAtlas, June 2010).…”
mentioning
confidence: 99%
“…Thus, in both cases the loss of the segment between the two furin cleavage sites is not likely to be an obligatory mechanism of ENaC activation by ␣ cleavage. Such built-in redundancy into channel cleavage would certainly be consistent with the ability of multiple diverse proteases such as trypsin, subtilisin, elastase, prostasin, furin, and plasmin to activate ENaC in different systems with a similar final outcome (9,24,(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 68%